Analysis of the use of Information Technology in rural communities - Rifka Sinaga (Jurnal Komputer Indonesia (Ju-Komi), 2024)
This study aims to analyze the use of Information Technology (IT) in rural communities. Amidst rapid technological developments, rural communities have also begun to adopt IT, although they still face various obstacles such as limited infrastructure and low digital literacy. Through literature studies and previous research, it was found that the use of IT has had a significant impact on rural communities, including social, economic changes, and access to health and education services. However, greater efforts are still needed to increase IT adoption in rural areas and overcome existing obstacles. Further research is also needed to better understand the factors that influence IT adoption and its long-term impact on rural development. Thus, this study is expected to provide valuable insights for policy makers, practitioners, and academics in efforts to improve digital inclusion and the welfare of rural communities.